Analysis to Users’ Reaction on Weird 3D Animation Videos on Instagram - Qurrotul. A., Erni D., Nurhasanah, Bella M., (University of Respati Yogyakarta, Indonesia, 2019)
Currently, Instagram is the most favorite social media platform in Indonesia and Instagram is already ranked as the 7th largest social media worldwide with the number of users around 800 million in January 2018 (Wearesocial.net, 2018). The main purpose of Instagram is to channel users? visual ideas in the form of photos, digital arts, and videos. Besides, Instagram can also be a promotion tool for art. Here, users can find accounts with out-of-the-box contents, which tend to be disgusting or weird. One of the examples is @extraweg which produces 3D Animation videos. The content creator uploads digital arts which successfully attract Instagram users? attention, resulted in both positive or negative reactions. Therefore, this research aims to study users? reactions to some of the most viewed videos uploaded by @extraweg content creators. The result shows that there are pros and cons from the users. Pro comments on @extraweg?s account show that people love and satisfy with its 3D animation artworks. On the other hand, there are people who feel uncomfortable with the videos.